Analisis Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Koperasi UMKM Perindustrian Kabupaten Agam - Nofriadiman; Vernando, Feri; Latif , Abd. (Riset Sinergi Indonesia, 2023)
Work environment is everithing around of employee or official when they’re doing for the job, that is physical or nonphysical environment, that can influanced employee or official and their job. Physical environment in the office or company is the work condition to give an atmosphere and confortable work situation to get the destination of office and company.The work environment at Dinas Koperasi UMKM Perindustrian Perdagangan Kabupaten Agam is not so conducive, this is cause of the temperature is warm it’s about 25ºC- 33ºC, the room lighting is not equally it’s about 50 lux until 165 lux, the air circulation is no so fine, the noice because the room of all sector just bordered by partition it’s about 150 cm, the layout of the room is not so arranged, the room sanitation is not kept, and the proponent fasilities is not complete. Base on the data tabulation 6 variables of work environment (X1= room temperature, X2= room lighting, X3= room layout, X4= room noice, X5= air sirculation, dan X6= room sanitation) only one variable is gift the significant influance to the official performance, that is room temperature (X1) by the regression coeficient is 0,548, the meaning when the room temperature is adding about 0,548 then work environment give the significant inluance to the official performance is 0,548. So the head master office of Dinas Koperasi UMKM Perindustrian Perdagangan Kabupaten Agam have to repair and improvement the work environment especially the room temperature (X1) to make the conducive work enviroment